Channel 4 and the declining influence of organized religion on UK television. The case of Jesus: The Evidence. Issue 4 (1st October 2016) - Wallis, Richard
Abstract : During the early 1980s, there was a high level of expectation attached to the provision of a fourth television service in the UK. Channel 4 was set up to be a publisher–broadcaster, commercially self-funding, but with a public service remit to cater for minority groups. For the churches, the new channel initially looked as if it might provide fresh impetus for religious broadcasting, believed by many to be moribund. The paper examines the circumstances surrounding Jesus: The Evidence, a highly controversial Easter documentary series commissioned by Channel 4 during its first year – not at all what the churches had hoped for. It is suggested that the public furore sparked by the series arose from an escalating sense of disentitlement related to a very particular earlier history. It charts the general shift away from the precedent established in the 1920s by the BBC's first Director General, to the advent of Channel 4, by which time this earlier position had come to be viewed as less than impartial. The paper identifies the principal points of contestation at the heart of the controversy, and concludes that it was emblematic of a growing cultural dissonance between the religious and the broadcasting institutions.